Healthcare Worker Burnout and Organizational Management Practices: A Systematic Review of Preventive Interventions - Achmad Aprianor Firdaus; Rusmiati Rusmiati; Elmia Kursani (Brilliant International Journal Of Management And Tourism, 2025)
Performance management systems (PMS) play a crucial role in healthcare organizations by influencing staff motivation and ultimately affecting patient care quality. However, the relationship between PMS implementation and its impact on healthcare outcomes remains fragmented in the literature. This systematic review aims to synthesize current evidence on the effectiveness of performance management systems in healthcare organizations, specifically examining their impact on staff motivation and patient care outcomes. A comprehensive systematic review was conducted following PRISMA guidelines. Electronic databases including PubMed, Scopus, Web of Science, and SINTA were searched from January 2000 to December 2024. Studies examining performance management systems in healthcare settings and their effects on staff motivation and patient outcomes were included. From 847 initial records, 28 studies met the inclusion criteria. The review identified that well-implemented performance management systems showed positive associations with staff motivation (effect size: 0.67, 95% CI: 0.45-0.89) and patient care quality metrics (effect size: 0.58, 95% CI: 0.38-0.78). Key components of effective PMS included regular feedback mechanisms, goal alignment, and competency-based evaluations. Performance management systems demonstrate significant potential in enhancing both staff motivation and patient care quality when appropriately implemented. Healthcare organizations should focus on developing comprehensive, fair, and transparent PMS that align individual goals with organizational objectives.